PERAN KEWIRAUSAHAAN DALAM MENINGKATKAN KESEJAHTERAAN EKONOMI SEROJA TIMUR - Ahmad Nizar Yogatama; Sri Anggraini Kusuma Dewi (Fakultas Ekonomi Universitas 45 Surabaya, 2016)
Role of Entrepreneurship in Eastern Seroja very important in the realization of an increase in economic welfare. The purpose of this study is to see how far the entrepreneurial role in improving the economic welfare of residents in the Village East Seroja Mergosono Kedungkandang District of Malang. (1) the role of entrepreneurship for Eastern Seroja; (2) the representation of entrepreneurship in East Seroja; (3) problems faced by Lotus East. The results showed that entrepreneurial attitudes and behaviors shaping innovative proactive, representation of the attitudes and the behavior is the Chairman of the PKK and its citizens East Seroja applying social entrepreneurship. The problem faced is the first, yet animating entrepreneurial profession. Second, entrepreneurs simply to raise revenue. Third, self-employment is not considered a stable job. Fourth, the majority of entrepreneurs are Housewife. Fifth, afraid to use e-commerce. Sixth, the majority of entrepreneurs are more comfortable using mouth-to-mouth.